Outcomes and occurrence of post-operative pulmonary hypertension crisis after late referral truncus arteriosus repair - Zhu, Yifan; Jiang, Qi; Zhang, Wen; Hu, Renjie; Dong, Wei; Zhang, Hao; Zhang, Haibo (Frontiers in Cardiovascular Medicine, 2022)
Background: Truncus arteriosus (TA) is a rare congenital heart disease with high early mortality. The occurrence of postoperative pulmonary hypertension crisis (PHC), known to be a common and life-threatening complication, increases due to irreversible development of pulmonary vascular resistance with ages. We sought to figure out the risk factors for PHC and describe the surgical outcomes of TA patients with late referral (>1month excluded). Methods: We retrospectively reviewed patients after TA repair between 2009–2021 at Shanghai Children’s Medical Center. The occurrence of PHC was defined according to postoperative Pp/Ps≥1 and clinical manifestations. Risk factors for PHC and mortality were conducted by multivariable analysis. Results: A total of 98 patients were treated, including 55 males and 43 females. Median age at repair was 121(69, 245) days. Postoperative PHC occurred in 22(22.4%) patients with a median age of 186(122, 293) days. By multivariable analysis, patients with the sum of Z-score of preoperative bilateral pulmonary artery (PA) diameters (OR:1.6, 95%CI:1.2-2.3, P=0.01) was more likely to experience PHC. Longer CPB duration contributed to early death (OR:1.0, 95%CI:1.0-1.0, P=0.01). Total Survival at 10 years was 81.4%. Twenty-six patients received 30 reinterventions in 4.5(2.9, 7.5) years follow-ups. Valved reconstruction of RVOT most predicted reinterventions (OR:4.2, 95%CI:1.4-13.0, P=0.01). Conclusions: Surgical repair of TA patients with late referral has resulted in comparatively favorable early and mid-term outcomes. PHC occurred more common in patients with overextended bilateral PA preoperatively. Meanwhile valved reconstruction of RVOT would more likely lead to early reintervention.